The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1108/medar-10-2015-0065
|View full text |Cite
|
Sign up to set email alerts
|

Pink accounting in Italy: cultural perspectives over discrimination and/or lack of interest

Abstract: Purpose\ud The issue of gender inequality in the Italian universities and academic context does not seem to be particularly debated and is really rare. Starting from this “lack of interest”, the paper aims to inquire into the “state-of-the-art” of existing inequality in the scientific and academic path of Italian female scholars and academia, answering the following research question: Is discrimination between women and men linked to the number of scientific contributions in periodicals and their presence with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 59 publications
0
23
0
2
Order By: Relevance
“…For institution‐related research, Baldarelli et al . () examined gender equality in Italian universities and academic contexts.…”
Section: Analyses Of Recent Accounting Publicationsmentioning
confidence: 99%
“…For institution‐related research, Baldarelli et al . () examined gender equality in Italian universities and academic contexts.…”
Section: Analyses Of Recent Accounting Publicationsmentioning
confidence: 99%
“…Academia transforms the organizational, social, political, and psychological aspects. Many studies have identified gender inequality at universities (Baldarelli, Baldo, & Vignini, 2016;De Paola & Scoppa, 2015;Galizzi & Siboni, 2016). The lower promotion rate of women to full accounting professor at university is one reason that women are unwilling to choose academia (Gago & Mac ıas, 2014).…”
Section: Gender Inequality In Academiamentioning
confidence: 99%
“…The lower promotion rate of women to full accounting professor at university is one reason that women are unwilling to choose academia (Gago & Mac ıas, 2014). Women's career progress in academia in Italy is also hindered, so women's contributions to gender discourse on accounting was found to be less than that of men (Baldarelli et al, 2016).…”
Section: Gender Inequality In Academiamentioning
confidence: 99%
“…Several studies and contributions attested to the gendered nature of accounting organisations (Hines 1992;Loft 1992;Lehman 1992;Kirkham and Loft 1993;Fogarty et al 1998;Grey 1998;Napier 2001;Dambrin and Lambert 2006;Roberts 2013). Using these studies as a benchmark and starting point, other contributions began to emerge in the literature, mostly empirical studies of gender in accounting organisations and academia (Anderson-Gough et al 2002;Dambrin and Lambert 2006Lupu 2010;Kornberger et al 2010;Broadbent 1998Broadbent , 2016Komori 2007;Virtanen 2009;Samkin and Schneider 2014;Baldarelli et al 2016).…”
Section: Gendered Nature Of the Accounting Professionmentioning
confidence: 99%